PROBLEMS OF TRANSPORT LOGISTICS DEVELOPMENT IN UKRAINE UNDER MARTIAL LAW - Shevchenko, Iryna; Klyus, Iryna (Science-based technologies, 2023)
The study considered the problems of modern logistics business in Ukraine, drew parallels with the main trends that were formed in the world during the coronavirus period, and considered the main directions of logistics flows and ways of their transformation due to the general international situation. In the study, it was determined that the so-called strategy of localization of logistics business began to take shape in the world, focused on the clustering of factories, transport companies, and especially consumers mainly in one region in order to avoid the risks of disruption of production and the impossibility of meeting the needs of consumers. The world is actively moving from the concept of "delivery on time" to "delivery on demand". This is another step towards system-wide resilience and flexibility. Perhaps in the future, a more radical shift from goods to services will ease the burden on supply chains. But now debates about various forms of cooperation, such as nearshoring, onshoring, and transfer of business processes to other regions, are becoming relevant again. In addition to global problems, others appeared, such as a shortage of rolling stock reoriented to military needs, and a shortage of personnel rejected by the war. However, some problems were solved quite quickly: the 70-year-old problem of the difference in railway tracks, the restoration of rolling stock with the help of Western partners and volunteers, and alternative supply routes. Thus, it can be noted that the war in Ukraine only exacerbated the problems that were brewing in international logistics transportation during the coronavirus period. However, the conducted studies have shown that Ukrainian logistics transport quite successfully solves these problems and the problems of relocation of the warehouse network. But such an approach requires the development of a certain algorithm of coordinated actions, which must be optimized taking into account the economical use of resources.